PENENTUAN PENERIMA BANTUAN BERAS RASKIN PADA DESA SINDANGHAYU MENGGUNAKAN METODE VIKOR - Sugiarto, Agung; Rizky, Robby; Wibowo, Andrianto Heri; Susilawati, Susilawati; Pratama, Aghy Gilar; Wardah, Neli Nailul; Hakim, Zaenal; Setiyowati, Sri; Yunita, Ayu Mira; Susanti, Ervi Nuraflian (Universitas Mathla’ul Anwar Banten, 2023)
In this research, we discuss the VIKOR method system to facilitate the identification process of RASKIN rice aid recipients in Sindanghayu Village. The VIKOR method is used to select potential aid recipients considering several important criteria. This study first identified the criteria for determining RASKIN rice assistance recipients, including the number of family members, per capita income, health status and food needs. In addition, data on these criteria were collected from each household in Sindanghayu Village. The families of potential funding recipients are then analyzed and compared using the VIKOR method based on defined criteria. In this phase, the criteria are weighted using the AHP (Analytical Hierarchy Process) technique to determine the level of importance of each criterion. Families are then evaluated using the VIKOR method based on the level of importance and the relationship between the criteria. The results of the VIKOR analysis can give the highest priority to potential aid recipients who meet higher weighting criteria. In this way, the identification of the RASKIN rice aid beneficiaries in Sindanghayu Village can be carried out more objectively, effectively, and efficiently.